Immunogenicity and safety of a nine-valent human papillomavirus vaccine in women 27–45 years of age compared to women 16–26 years of age: An open-label phase 3 study. Issue 20 (12th May 2021) - Joura, Elmar A.; Ulied, Angels; Vandermeulen, Corinne; Rua Figueroa, Milagrosa; Seppä, Ilkka; Hernandez Aguado, Juan José; Ahonen, Anitta; Reich, Olaf; Virta, Miia; Perino, Antonino; Peris Tuser, Merce; Peters, Klaus; et al.
Highlights: We compared 9vHPV vaccine immunogenicity in women 27–45 vs 16–26 years of age. 9vHPV vaccine elicited noninferior anti-HPV antibodies in mid-adult vs young women. 9vHPV vaccine was well tolerated in both groups of women. Data support bridging of 9vHPV vaccine efficacy from young to mid-adult women. Abstract: Background: Efficacy of the nine-valent human papillomavirus (9vHPV; HPV types 6/11/16/18/31/33/45/52/58) vaccine was demonstrated in a phase 3 study in women 16–26 years of age. We present a phase 3 immunogenicity and safety study of the 9vHPV vaccine in women 27–45 versus 16–26 years of age. Methods: This international, open-label study (NCT03158220) was conducted in women 16–45 years of age. Participants (16–26 years, n = 570 and 27–45 years, n = 642) received a three-dose 9vHPV vaccination regimen (day 1, month 2, month 6). Month 7 geometric mean titers (GMTs) and seroconversion percentages to anti-HPV 6/11/16/18/31/33/45/52/58 were assessed. Participants were followed for safety throughout the study. Results: At month 7, anti-HPV 6/11/16/18/31/33/45/52/58 GMTs in women 27–45 years were compared to those in women 16–26 years of age. The primary hypothesis of non-inferiority of anti-HPV 16/18/31/33/45/52/58 GMTs in older versus younger women was met. The lower bound of the GMT ratio 95% confidence interval (27–45 years to 16–26 years) was 0.60–0.67 depending on HPV type, exceeding the non-inferiority margin of 0.5 for all HPV types. Month 7 seroconversion percentages in women 27–45 years of age were >99% for all HPV types. Injection-site and vaccine-related systemic adverse events (AEs) were observed in 87.5% and 25.1% of women 16–26 years, and 85.2% and 24.1% of women 27–45 years of age, respectively; no vaccine-related serious AEs were reported and no deaths occurred during the study. Conclusions: The 9vHPV vaccine elicited non-inferior anti-HPV GMTs in women 27–45 years compared with women 16–26 years of age for HPV 16/18/31/33/45/52/58. The vaccine was generally well tolerated with a similar AE profile across the age groups. These data support bridging 9vHPV vaccine efficacy findings in women 16–26 years to women 27–45 years of age. Clinical trial registration NCT03158220.